Pendidikan Ibu Berhubungan dengan Teknik Menyusui pada Ibu Menyusui yang Memiliki Bayi Usia 0-12 Bulan - Nur Indah Rahmawati (Alma Ata University Press, 2017)
In developing countries there is a 20% from 35.6% a mother that failed in breastfeeding proces. Based on the Riskesdas In 2010, there were 67.5% of mothers breastfeeding their babies fail due to lack of understanding of mothers about breastfeeding technique. The research aimed to determine the factors associated with breastfeeding technique at breastfeeding mother who has Infants age 0-12 months in Bina Sehat Clinic Kasihan Bantul Yogyakarta. This research uses descriptive analytic method. The population in this study are all breastfeeding mothers with babies aged 0-12 months. Sampling using qouta sampling with total sample of 58 respondents. Analysis of the data used univariate and bivariate analysis using chi-square analysis. The results based on the characteristics of nursing mothers, respondents have 20-35 years of age, high school educated, have jobs as housewife and have parity>2. The majority of respondents did breastfeeding technique is still one (51.7%). Breastfeeding technique has the highest value is when the mother drive the baby to the mother's breast and nipple and areola enter as many (89.7%), while respondents who had the lowest score in the breastfeeding technique is when washing your hands, the way a mother holding a baby, baby's body closer to the stomach, and a sign of the baby sucking properly. Results of cross tabulation shows that education is associated with feeding techniques with p=0.029, while other factors are associated with feeding techniques age p=0.847, p=0.940 parity; p=0,311 jobs. Conclusion of the study stated that education is associated with feeding techniques with p=0.029 and the majority of respondents still wrong in doing the correct breastfeeding technique that needs to be done counseling by health professionals, especially midwives in order to find out how breastfeeding technique is good and right.